Vínculo na estratégia saúde da família na perspectiva de usuários e profissionais de saúde - Gabrielli Pinho de Rezende (2015)
This is a qualitative case study that aims at identifying link building strategies between health professionals and users of Family Health Units. This study took place at three health care units in the city of Paraopeba. Three doctors, three nurses, three nursing technicians, six community health workers, two managers (key informants) and seventeen users participated in the study. Data was collected through non-participant observation recorded in a field diary and semi-structured interviews. Data was analysed using Thematic Content Analysis and organized in three categories; the second and the third categories comprised three and two sub-categories, respectively: 1. Expressions of the bond in everyday life it identifies the concepts of bonding reported by the participants; 2. Expectations of this relationship: the view of users, professionals and management - it presents the objectives and different perspectives of users, managers and professionals about the professional/user relationship; 2.1. Good service and resolvability ensure users follow-up; 2.2. Feeling of belonging: involvement and health; 2.3. Changes in relationships generate changes in the health care model; 3. Building bonds shows the steps taken to build continuous bonds and some of the obstacles still present; 3.1. Common steps towards a better health care; 3.2. And the journey continues The study results demonstrate that regardless of the formulation of a concept, bonding is experienced by health professionals and users in Paraopeba and that workplace stability and reduced turnover amongst health professionals would favour the building of attachments. The different views of managers, health professionals and users about the professional/user relationship can indicate the existence of conflicting objectives that may jeopardise the delivery of comprehensive health services. A closer contact with the user contributes to quality health care; however, obstacles to the continuity of the link still exist. The present study aims at broadening the reflection on, the planning and strengthening of that link in the Family Health Strategy programme.